A Brutality-Based Approach to Identifying State-Led Atrocities. (October 2022) - Cingranelli, David; Mark, Skip; Garvey, James B.; Hutt, Jordan; Lee, Yuri
The comparative study of atrocities and atrocity prevention faces several obstacles including a lack of consensus on the universe of cases and too few cases to statistically test alternative theories. The brutality-based (BB) conception is based on the idea that widespread, state-led violations of physical integrity rights constitute an assault on the personhood and human dignity of the members of society— a mass atrocity. Applying this idea to all countries annually systematically identifies a larger number of atrocities and facilitates categorization into three levels of intensity. The BB methodology for generating annual atrocity lists is replicable and transparent. The findings show that, between 1981 and 2019, the frequency of atrocities as defined and identified by other projects has been decreasing, but BB atrocities have been increasing. The sequence of different types of widespread physical integrity violations suggests new avenues for research on atrocity occurrence, escalation, de-escalation, and cessation.